Possible triggering of strong earthquakes in a seismic sequence due to Coulomb stress changes generated by the occurrence of previous strong shocks - PAPADIMITRIOU, E. E.; KARAKOSTAS, V. G.; BABA, A. B. (Bulletin of the Geological Society of Greece, 2001)
Coulomb stress changes (ACFF)were calculated assuming that earthquakes can be modelled as static dislocations in an elastic half-space, and taking into account the coseismic slip in strong earthquakes. The stress change calculations were performed for strike, dip, and rake appropriate to the strong events considered. We evaluate if these chosen earthquakes brought a given strong subsequent event closer to, or farther from, failure. It was found that each of the subsequent strong events occurred in regions of increased calculated Coulomb stress before their occurrence. Moreover, the majority of smaller aftershocks also were located in areas of positive ACFF. This indicates the probable triggering of the latter events, the foci of which are situated at nearby faults or fault segments.